2008
DOI: 10.1083/jcb.200709061
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperone Hsp90 stabilizes Pih1/Nop17 to maintain R2TP complex activity that regulates snoRNA accumulation

Abstract: Hsp90 is a highly conserved molecular chaperone that is involved in modulating a multitude of cellular processes. In this study, we identify a function for the chaperone in RNA processing and maintenance. This functionality of Hsp90 involves two recently identified interactors of the chaperone: Tah1 and Pih1/Nop17. Tah1 is a small protein containing tetratricopeptide repeats, whereas Pih1 is found to be an unstable protein. Tah1 and Pih1 bind to the essential helicases Rvb1 and Rvb2 to form the R2TP complex, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
252
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(274 citation statements)
references
References 53 publications
11
252
0
6
Order By: Relevance
“…Thus, the IP-and biotin-GA-mediated purification of structural proteins, including tubulin and kinesin, provides further evidence for the involvement of Hsp90 in the assembly of the tubulin-based cytoskeleton network, cytokinesis, and cellular transport (McClellan et al 2007;Te et al 2007). Isolation of RNA-binding proteins and ribosomal subunits points to the suggested role of Hsp90 in ribosomal subunit nuclear export and RNA processing and maintenance (Schlatter et al 2002;Zhao et al 2008). Similar to Falsone et al, we identified several metabolic enzymes (Falsone et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the IP-and biotin-GA-mediated purification of structural proteins, including tubulin and kinesin, provides further evidence for the involvement of Hsp90 in the assembly of the tubulin-based cytoskeleton network, cytokinesis, and cellular transport (McClellan et al 2007;Te et al 2007). Isolation of RNA-binding proteins and ribosomal subunits points to the suggested role of Hsp90 in ribosomal subunit nuclear export and RNA processing and maintenance (Schlatter et al 2002;Zhao et al 2008). Similar to Falsone et al, we identified several metabolic enzymes (Falsone et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Comprising about 1% of all cellular proteins, Hsp90 is involved in diverse processes ranging from processing and maintenance of RNA to protein sorting and assembly of the tubulin-based cytoskeleton network (Te et al 2007;Lotz et al 2008;Zhao et al 2008). However, one of the most exciting roles of Hsp90 is the stabilization of a set of client proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of the Nop17 gene led to dissociation from the nucleolus of all 4 box C/D snoRNP, Nop1, Nop56, Nop58, and snu13 and accumulation of pre-rRNA 35 S . Notably, Pih1/Nop17 is also an unstable protein with a propensity to aggregate in the absence of Tah1 and Hsp90 (Zhao et al 2008).…”
Section: Pih1d1 (Pih1/nop17)mentioning
confidence: 99%
“…Although the exact function of these factors remains elusive, one of these RPAPs, RPAP3, is part of an 11-subunit protein complex that we termed the RPAP3/R2TP/prefoldinlike complex (Fig. 1) based on similarity to the previously characterized R2TP complex, a cofactor of Hsp90 (Zhao et al 2008), and prefoldin complexes (chaperone associated with the CCT/TRiC complex) (Geissler et al 1998;Vainberg et al 1998). Similar complexes have been described in two independent reports.…”
Section: Introductionmentioning
confidence: 99%
“…Pih1 (Protein interacting with Hsp90), which belongs to Pih1 family of proteins, directly interacts with Rvb1-Rvb2 complex (Rvbs) and Tah1 (TPR [tetratricopeptide repeat-containing protein] associated with Hsp90) (1,3,6). In yeast, Pih1 is an unstable protein and prone to aggregate in vitro, however, the Pih1 aggregates are dissociated by Hsp90 in an ATP-dependent manner, and its disaggregation activity of Hsp90 is enhanced by Tah1 (6). Tah1 is suggested to function as a co-chaperone of Hsp90 in disaggregating Pih1 (6).…”
Section: Introductionmentioning
confidence: 99%